ASME 2009 Dynamic Systems and Control Conference, Volume 1 2009
DOI: 10.1115/dscc2009-2705
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phenotypic State Transition Probabilities in Living Cells

Abstract: Living cells stochastically switch their phenotypic states in response to environmental cues to maintain persistence and viability. Estimating the state transition probabilities from biological observations of cell populations gives valuable insight to the underlying processes, and gives insights as to how the transition statistics are influenced by external factors. In this work, we present two Bayesian estimation approaches. The first is applicable when individual cell state trajectories are observed. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In [7] we have shown that in order to satisfy equality constraint (12), we sample from a distribution characterized by…”
Section: B Constrained Gaussian Sampling: Equality Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [7] we have shown that in order to satisfy equality constraint (12), we sample from a distribution characterized by…”
Section: B Constrained Gaussian Sampling: Equality Constraintsmentioning
confidence: 99%
“…In [7], we developed Bayesian estimation schemes for addressing both estimation problems (using panel and longitudinal data). A tacit assumption was that, in both formulations, the state transitions are synchronous among the population members, and are also synchronous with the observations.…”
Section: Introductionmentioning
confidence: 99%
“…For simplicity, we ignore phenotypic state, except for the distinction between tip and stalk cells. For more details on modeling and identification of phenotypic state, see [5,9].…”
Section: Dynamic Modeling Overviewmentioning
confidence: 99%
“…Computing transition probabilities is a rather straightforward problem if time lapse data of phenotype state transitions are available. Although migration states are easy to detect from time lapse trajectory data, differentiating the quiescent state from proliferative and apoptotic states is difficult, and has been a research issue (Farahat and Asada, 2009). In this paper we assume that such phenotype transition data are available.…”
Section: Estimation Of Phenotype State Transition Probabilitiesmentioning
confidence: 99%